APLIKASI NIHSS PADA PASIEN STROKE DI RUANG TRIAGE INSTALASI GAWAT DARURAT RS DR. ISKAK TULUNGAGUNG - Saudin, Didik; Rajin, Muhammad (Jurnal EDUNursing, 2017)
Abstract Background : Stroke cases in Indonesia increased each year in East Java, the number of casestroke by 16% increase. The success of stroke treatment is highly dependent on the speed, accurand precision at the beginning of the incident. Based on the existing cases of stroke, we need comprehensive assessment methods, it aims to determine the appropriate action in stroke patiso that they can to minimize the severity of the stroke. Assessment of the National InstituteHealth Stroke Scale (NIHSS) is the first step of the nursing process to gather accurate datorder to minimize the degree of disability and death in the case of stroke. Methode: Ustatistical analysis between the appraiser, determined reliability intraclass correlation coefficcaracteristic (ICC) using ANOVA. Retrospective represent clinically relevant values. Receoperator characteristic (ROC) was used as the NIHSS assessment accuracy. Result: Clinicallstatistically significant differences between the estimates of the average score in accordance the six assessors (ANOVA: overall P=0.15, log P=0.28, debit P=0.59). Couple assessors excellent ICCs ranging from 0.70 to 0.89. pair of assessors over 90%. Estimated value of NIwere within 5 points with a high degree of reliability and validity. Conclusion: NIHSS designed as a tool to measure stroke patients. this scale to evaluate sharpness stroke patientdetermine the proper treatment, and predict the outcome of stroke patients. Keyword : NIHSS, Spesifikasi Stroke